2012
DOI: 10.4103/0378-6323.98095
|View full text |Cite
|
Sign up to set email alerts
|

Computer Assisted Objective Structured Clinical Examination: A useful tool for dermatology undergraduate assessment

Abstract: CA-OSCE is a useful tool for assessment of dermatology undergraduates. It has the potential to drive them to attend regularly as well as to test their higher cognitive skills of analysis and problem solving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Grover et al, [2] have previously documented the use of a computer assisted OSCE (CA-OSCE) for undergraduate dermatology assessment and their study showed good acceptance by the students. This study highlighted the importance of considering such a method in the situation of shortage of faculty in dermatology teaching institutes.…”
Section: Discussion Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Grover et al, [2] have previously documented the use of a computer assisted OSCE (CA-OSCE) for undergraduate dermatology assessment and their study showed good acceptance by the students. This study highlighted the importance of considering such a method in the situation of shortage of faculty in dermatology teaching institutes.…”
Section: Discussion Discussionmentioning
confidence: 93%
“…However, it was not documented how well the OSCE correlates to overall performance of the student. [2] While the OSCE is definitely more objective compared to other more traditional methods like case presentations, equal importance should be given to other aspects related to reliability and validity. One of the most important factors which increases reliability would be to increase the number of slides.…”
Section: Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital modules, problem-based learning, and objective structured clinical examination (OSCE) style teaching have all been reported in the literature, and the use of standardized patients consistently appears to be an effective way of teaching dermatology. 6,7 In fall 2015, the University of Toronto Division of Dermatology restructured the undergraduate medical education curriculum, moving away from didactic lectures and 3 half-days of clinics and transitioning toward online modules with a large-scale, 32-station patient-viewing education program.…”
Section: Introductionmentioning
confidence: 99%
“…Digital modules, problem-based learning, and objective structured clinical examination (OSCE) style teaching have all been reported in the literature, and the use of standardized patients consistently appears to be an effective way of teaching dermatology. 6,7…”
Section: Introductionmentioning
confidence: 99%